Lessons from the Recent Macroeconomic Crisis: Theoretical Explanation - Landais , Bernard (Studia Oeconomica Posnaniensia, 2026)
This paper starts from the recent crisis and its lessons for understanding the causes of the disequilibria and fluctuations. The intention is to observe and inform the macroeconomic processes with a combined view on monetary policy. It endorses the main ideas expressed by the three equation model of the New Neo-Keynesian Synthesis, to which one loanable funds equation is added. In addition, it also emphasizes non-orthodox forms of central bank policies. This new four equation model is used to make the macroeconomic relationships clear in the short run for "normal» periods. Furthermore, it is a convenient starting point for studying economic and financial crises with a very strong indication of relevant anticipations and risks in the Austrian, Leijonhufvud or Minskyan traditions.